IVF/ICSI efficiency in women with Hashimoto thyroiditis - Сафарян, Галина; Гзгзян, Александр; Джемлиханова, Ляиля; Ниаури, Дарико (Вестник Санкт-Петербургского университета. Медицина, 2020)
It is known that in women affected with thyroid autoimmunity, namely Hashimoto’s thyroiditis, the prevalence of infertility is very high and reaches 47%. The retrospective cohort study was performed to assess the effects of thyroid autoimmunity on IVF/ICSI outcomes in women with infertility due to tubal factor and verified autoimmune thyroiditis in status of euthyroidism. The present study confirms a negative impact of thyroid autoimmunity on the course of pregnancy achieved through IVF/ICSI. Thyroid autoimmunity does not appear to have an impact on IVF/ICSI outcome in terms of mean number of oocytes retrieved. However, fertilization, implantation and delivery rates were lower, and the risk of miscarriage was higher in the presence of anti-thyroperoxidase autoantibodies. Thus, thyroid autoanantibodies positivity even in euthyroid state should be considered an independent risk factor for pregnancy complications after IVF/ICSI treatment.